A novel fractional order proportional integral derivative plus second-order derivative controller for load frequency control - Khokhar, Bhuvnesh; Dahiya, Surender; Parmar, K. P. Singh (International journal of sustainable energy, 2021)
This paper proposes a novel fractional order proportional integral derivative plus second-order derivative (FOPID+DD) controller for the load frequency control (LFC) of a hybrid power system (hPS). The investigated hPS incorporates conventional and certain distributed generation sources. Parameters of the proposed controller are optimised using a newly developed and powerful water wave optimisation (WWO) algorithm. The effectiveness of the proposed control scheme is established by considering multiple disturbances and nonlinearities like generation rate constraint, governor dead band and time delay related with the hPS. The performance of the proposed controller is compared with other controllers that are well studied in the literature. Simulation results reveal that the frequency dynamics of the hPS are enhanced with the proposed controller in terms of reduced frequency deviations and improved transient specifications. The sensitivity of the proposed controller is validated subject to wide variations in the hPS parameters.